Razones para ser y hacer con los otros en nuestra sociedad posmoderna - Martín Estalayo, Maribel (Cuadernos de Trabajo Social, 2007)
Social Work with groups or Social Community Work is not easy to support without the approach to human being experiences in their current context. Talking about the person and their relations means that it’s necessary to try to understand their life strategies considering the circumstances in life process. This work is dealing with an approach to our postmodern society characteristics in order to facilitate the knowledge of new facts that support reasons for being and acting with others.